Penguasaan Tanah Reklamasi tanpa Alas Hak atas Tanah: Studi Kasus di Desa Taddan, Kecamatan Camplong, Kabupaten Sampang - Amri Ubaidillah (Lentera Hukum, 2018)
This study discuss legal issues concerning control of reclamation without possessing land rights as the result of the unregistered reclamation by communities in the Village of Tanddan, Sub-district Campling in the Sampang Regency. The aim of this study is to show legal implications and analyze effectivity of law enforcement on the accomplishment land control of reclamation without possession. By using empirical legal research with socio-juridical approach, the result of study shows that legal subject cannot control over and build houses over land of reclamation withou posession of land rights. In other words, houses built over land of reclamation without land rights can be evicted without any compensation. Therefore, such land of reclamation should be registered as the governmental land to the National Agrarian Board or Badan Pertanahan nasional (BPN) in the Sampang regency. It also affirms that there is a problem of effeciency of law enforcement on the accomplishment of land control of reclamation without any repressive and preventive measures. Keywords: Land Control, Reclamation, Sampang